2010
DOI: 10.1111/j.1439-0418.2009.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of systemic potato response to wounding and jasmonate on the aphid Macrosiphum euphorbiae (Sternorryncha: Aphididae)

Abstract: Plant induced responses are activated by multiple biotic and abiotic stresses, and may affect the interactions between a plant and phytophagous insects. The objective of this work was to evaluate the effects of different stresses inflicted to potato plants (Solanum tuberosum) on the potato aphid (Macrosiphum euphorbiae). Abiotic wounding, biotic wounding by Leptinotarsa decemlineata and treatment with volatile methyl jasmonate (MeJA) were evaluated with regard to the orientation behaviour, the feeding behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 54 publications
(58 reference statements)
0
16
0
Order By: Relevance
“…In addition to known phytochemicals, the tissue would have an array of other inducible defenses present, which could potentially function synergistically in defense against ECB herbivory. Inducible plant defenses often effectively increase resistance against insect feeding by reducing insect growth and decreasing fecundity (Agrawal 1999;Bruinsma et al 2007;Abe et al 2008Abe et al , 2009Stout et al 2009;Brunissen et al 2010). In contrast, plants that are deficient in JA signaling and have a compromised defense response are far more susceptible to insect feeding (Halitschke and Baldwin 2003;Abe et al 2008Abe et al , 2009Scott et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to known phytochemicals, the tissue would have an array of other inducible defenses present, which could potentially function synergistically in defense against ECB herbivory. Inducible plant defenses often effectively increase resistance against insect feeding by reducing insect growth and decreasing fecundity (Agrawal 1999;Bruinsma et al 2007;Abe et al 2008Abe et al , 2009Stout et al 2009;Brunissen et al 2010). In contrast, plants that are deficient in JA signaling and have a compromised defense response are far more susceptible to insect feeding (Halitschke and Baldwin 2003;Abe et al 2008Abe et al , 2009Scott et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, the numbers of grain aphid (Sitobion avenae Fabricius) were reduced in plots of winter wheat treated with CJ (Birkett et al, 2000;Bruce et al, 2003). Using our study model, Brunissen et al (2010) reported that potato treatment with MeJA, which is JA volatile derivative, reduced the fecundity of M. euphoribae and further prolonged its pre-reproductive period. Likewise, induced tomato plants drastically reduced the reproductive rate of M. euphorbiae (Guerrieri et al, 2004).…”
Section: Cis-jasmone Negatively Impacts Aphid Performancementioning
confidence: 66%
“…Despite apparently lesser injuries inflicted by the aphid, Myzus persicae (Sulzer) (Homoptera: Aphididae), a greater number of volatiles were released, perhaps due to pathogen infection. Aphids were also unaffected by preliminary CPB wounding, suggesting that the presence of CPB does not influence the colonization behavior of Macrosiphum euphorbiae (Thomas) (Homoptera: Aphididae) [ 97 ].…”
Section: Interspecific Interactionsmentioning
confidence: 99%